Draft Genome Sequence of a New Delhi Metallo-β-Lactamase (NDM-1)-Producing Providencia stuartii Strain Isolated in Lima, Peru - Lezameta, Lizet (Microbiol Resour Announc, 2020)
Providencia stuartii is an opportunistic pathogen of the Enterobacteriales order. Here, we report the 4,594,658-bp draft genome sequence of a New Delhi metallo-β-lactamase (NDM-1)-producing Providencia stuartii strain that was isolated from an emergency patient in a private clinic in Lima, Peru.